Why I cook - Colicchio, Tom; Stein, Joshua David (Artisan, 2024)
"Tom Colicchio cooked his first recipe at 13 years old - a stuffed eggplant from an issue of Cuisine magazine that he picked up out of boredom - and it changed his life. Now for the first time ever, Tom recounts the extraordinary personal journey that brought him from his working-class Italian background in Elizabeth, New Jersey, to the award-winning kitchens of New York City's best restaurants to the stage of the Emmy Awards. Through 10 memoir chapters and 60 recipes, Why I Cook shares Tom's personal reflections of more than 40 years behind the stove"--